The Role of the Detergent Micelle in Preserving the Structure of Membrane Proteins in the Gas Phase1. (18th February 2015) - Reading, Eamonn; Liko, Idlir; Allison, Timothy M.; Benesch, Justin L. P.; Laganowsky, Arthur; Robinson, Carol V.
Abstract Despite the growing importance of the mass spectrometry of membrane proteins, it is not known how their transfer from solution into vacuum affects their stability and structure. To address this we have carried out a systematic investigation of ten membrane proteins solubilized in different detergents and used mass spectrometry to gain physicochemical insight into the mechanism of their ionization and desolvation. We show that the chemical properties of the detergents mediate the charge state, both during ionization and detergent removal. Using ion mobility mass spectrometry, we monitor the conformations of membrane proteins and show how the surface charge density dictates the stability of folded states. We conclude that the gas‐phase stability of membrane proteins is increased when a greater proportion of their surface is lipophilic and is consequently protected by the physical presence of the micelle.